Investigation of drying kinetics and qualities of turkey berry in fluidized bed dryer. (2021) - Barathiraja, R.; Thirumal, P.; Thirumalaikumarasamy, D.; Kajavali, A.; Ashokkumar, M.; Thiyagaraj, J.
Abstract: In this work, drying kinetics, physical and bio-chemical properties of turkey berry were studied at an air velocity of 3.6 and 4.2 m/s along with different temperatures of 70, 80, 90 °C as well as open sun drying. The parameters such as drying rate, effective moisture diffusivity, activation energy, shrinkage, total color changes and Vitamin-C were analyzed in detail. The maximum moisture diffusivity of the sample was measured as 7.56 × 10 −10 m 2 /s, at 90 °C with velocity of 4.2 m/s. The minimum and maximum activation energy was found as 30.79 and 32.29 kJ/mol at an inlet fluidized velocity of 3.6 and 4.2 m/s. The minimum volumetric shrinkage of the product was observed at 90 °C with velocity of 4.2 m/s while the minimum color change and maximum Vitamin-C retention was observed at 70 °C with velocity of 4.2 m/s. The morphology of the dried turkey berries was investigated using scanning electron microscope.